Results of routine thoracic radiographic examinations rarely impact the plan to proceed with anesthetic procedures in dogs with presumed acute intervertebral disc herniation - Takedai, Teiko; Block, Nicole; Pinal, Karina M.; Frederick, Steven W. (Frontiers in Veterinary Science, 2024)
Acute intervertebral disc herniation (IVDH) is a common neurologic disease in dogs. Thoracolumbar IVDH constitutes an emergency because associated neurological clinical signs can be progressive, and prognosis is highly dependent on preoperative presence of deep pain perception. Pre-anesthetic thoracic radiographs are recommended and routinely performed to evaluate for potential pathology that could result in increased anesthetic risk or change in overall prognosis. However, due to the emergent nature of this disease, the weight of thoracic radiographic findings on advanced diagnostic imaging and surgical plans for these dogs is unknown. The objective of this study was to investigate the clinical benefit of performing thoracic radiographs prior to advanced spinal imaging and surgery for the acute non-ambulatory dogs with a T3-L3 myelopathy. Retrospective review of the medical records of dogs diagnosed with acute non-ambulatory T3-L3 myelopathies was performed for data collection. Age, body weight, and alteration of treatment plan were compared between the dogs with positive thoracic pathology identified on thoracic radiographs and those with negative thoracic pathology. Dogs with radiographic pathology diagnosed were more likely to have their treatment plans changed than dogs with no radiographic pathology (2/16 with pathology, 0/89 with no pathology). Radiographic diagnosis of pathology was associated with alteration of treatment plans (p=0.014). The odds of radiographic thoracic pathology were 4.6 times higher if the dog was aged 12 years or older. Performing routine thoracic radiography prior to advanced spinal imaging in presumed IVDH cases rarely resulted in a change to the treatment plan, though the practice may be clinically relevant in dogs 12 years of age or older.